A microeconometric analysis of factors affecting global value chain participation in Zimbabwe - Stein Masunda; Norman Mupaso (Cogent Economics & Finance, 2019)
Using firm-level data, this study explores the microeconomic factors affecting global value chain (GVC) participation in Zimbabwe. GVCs are important as a result of the fragmentation of global production across countries. As expected, firm size and credit financing are important determinants in fostering GVC participation. However, and quite surprising, foreign-owned firms in Zimbabwe participate less in GVCs when compared to domestically owned firms. Using data for 549 firms, this study postulates that if firm participation in GVCs is to be enhanced, access to credit for firms should be frictionless and firm growth-enabling environment and policies should be established. Summarily, the study postulates positive trade and financial linkages. Thus, access to credit and firm size are important in promoting intra-firm trade.
Keywords: 330; global value chain; trade; microeconometric; probit; logit